Activity density of spiders inhabiting the citrus field in Lahore, Pakistan - Tahir, H.; Butt, A.; Naheed, Rakhshanda; Bilal, M.; Alam, I. (2011)
A survey of the spiders associated with citrus fields of University of the Punjab, Lahore, Pakistan was conducted to identify potential biological control agents of citrus pests in the study area. A total of 1098 specimens belonging to 38 species, 22 genera and nine families were collected. Lycosidae was the most abundant family while Gnaphosidae was represented by highest number of species. The number of species gradually increased from January until the end of trapping session. Richness and diversity was highest in the month of June. However, evenness was highest during the month of January. It is concluded that a rich spider fauna exists in citrus fields of the study area. As spiders are potential biological control agents of citrus pests, so any practice that may disrupt this group should be avoided by the farmers.